The diversity of human relationships - Auhagen, Ann Elisabeth; Salisch, Maria von 1956- (Cambridge University Press, 1996)
Over the last decade there has been a growing interest in interpersonal relationships in the scientific community as well as in the general public. Until now, no volume has covered comprehensively different types of interpersonal relationships, such as the relationships between friends, lovers, colleagues or parents and children. Ann Elisabeth Auhagen and Maria von Salisch have addressed this gap in the literature with this volume, first published in German and later revised for an American audience. The Diversity of Human Relationships draws together findings from social, developmental and organisational psychology, sociology, biology, and the research on personal relationships. It reviews the multiplicity of research approaches and results on interpersonal relationships and how they change over the life span. It also elaborates the characteristics of the different types of relationships